2015
DOI: 10.1016/j.pharep.2014.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophic and antioxidant effects of silymarin comparable to 4-methylcatechol in protection against gentamicin-induced ototoxicity in guinea pigs

Abstract: Silymarin exerts superiority over 4-methylcatechol when recommended as protective agent against gentamicin ototoxicity based on its efficient neurotrophic and antioxidant activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 61 publications
3
4
0
Order By: Relevance
“…At the start point, there was non-significant variation between groups with normal ABR in all animals, while at the end point there was significantly increased ABR threshold compared to the start one. Our results in group 2 compared to group 1 showed absence of ABR response in 75% of animals indicating sever hearing loss, while others showed significant increase in wave III latency, wave V latency and significant ABR threshold increase which coincides with many studies [5,22,29] . The ABR results are matched with histopathology in light and SEM where there are variable degrees of HCs death, pathological changes in stria vascularis and degeneration of spiral ganglion which are in line with many studies [22,30,31] .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…At the start point, there was non-significant variation between groups with normal ABR in all animals, while at the end point there was significantly increased ABR threshold compared to the start one. Our results in group 2 compared to group 1 showed absence of ABR response in 75% of animals indicating sever hearing loss, while others showed significant increase in wave III latency, wave V latency and significant ABR threshold increase which coincides with many studies [5,22,29] . The ABR results are matched with histopathology in light and SEM where there are variable degrees of HCs death, pathological changes in stria vascularis and degeneration of spiral ganglion which are in line with many studies [22,30,31] .…”
Section: Discussionsupporting
confidence: 90%
“…Our results in group 2 compared to group 1 showed absence of ABR response in 75% of animals indicating sever hearing loss, while others showed significant increase in wave III latency, wave V latency and significant ABR threshold increase which coincides with many studies [5,22,29] . The ABR results are matched with histopathology in light and SEM where there are variable degrees of HCs death, pathological changes in stria vascularis and degeneration of spiral ganglion which are in line with many studies [22,30,31] . ROS role in gentamicin ototoxicity is documented in different studies [32,33] .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, these aminoglycoside drugs also continue to be used in view of their cost and effectiveness, and their ototoxicity usually limits the dose range of drugs [4,6]. GM is a cationic aminoglycoside that enters cells via endocytosis and forms a complex with iron, which drives the formation of free radicals and directly promotes the formation of ROS [7]. Recent reports show that antioxidant drugs can benefit patients with hearing loss, because hearing loss is produced by excessive generation of reactive oxygen species (ROS) in cells of the cochlea [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Silymarin (SM) is a flavonolignan mixture derived from the seeds of Silybum marianum L. Gaertn (milk thistle), with silybin as its main component (70%–80%) [1]. SM has been widely used as a hepatoprotective agent for a variety of acute and chronic liver diseases, due to its therapeutic effect based on its antioxidant [2], anti-inflammatory [3], immunomodulatory [4] and anti-viral activities [5]. Previous reports have shown that the efficacy of oral SM on liver function and chronic hepatitis C virus (HCV) load was low, due to its low bioavailability, extensive first pass metabolism and short life of flavonoids [6].…”
Section: Introductionmentioning
confidence: 99%